Disfigured faces: repudiation of images within public space - Palazuelos, Felix Rebolledo; Fonseca, Tania Mara Galli (MATRIZes, 2019)
This paper is about experiencing images as an interactive imagistic process, as ideated by Bergson in his book Matter and Memory through a dubious aspect of photographic portraiture in terms of its repudiated reception within public space. We present a series of photographs taken in four Latin American cities which depict intentionally defaced headshots. Engaging the works of Deleuze, Bergson, Benjamin, and Barthes, we advance that these photographs are documentary testimony of different reactions. The photographs urge us to move beyond what the disfigured faces mean as iconic signs, to see them instead as indicial of the dynamic interaction between the portraits and the anonymous disfiguring agents as an image.